ANALYTICAL METHOD DEVELOPMENT AND VALIDATION OF SODIUM PHENYLBUTYRATE AND TAURURSODIOL BY USING RP-HPLC IN BULK AND PHARMACEUTICAL DOSAGE FORM - RAYUDU, SUNIL; MANORANJANI, M.; ANITHA, D. (International Journal of Applied Pharmaceutics, 2026)
Objective: In order to assess Sodium Phenylbutyrate and Taurursodiol, two active pharmaceutical components, simultaneously, this study set out to create and validate a new RP-HPLC (Reverse Phase High Performance Liquid Chromatography) technique that was simple, responsive, and stable. Methods: An X-bridge phenyl column with dimensions 150x4.6 mm and a 3.5 µ was used in the chromatographic approach. The mobile phase consisted of acetonitrile and 0.1% triethyl amine with a pH of 2.5, adjusted with OPA (Ortho Phosphoric Acid) in a ratio of 40:60. Isocratic elution was used. The instrumental conditions were set to 1.0 ml/min with a detection wavelength of 266 nm using the PDA (Photo Diode Array) detector. Validation of the proposed method was carried out according to an international conference on harmonization (ICH) guidelines. Results: The calibration curves were linear, with a regression coefficient (R2) value of 0.999 and concentrations ranging from 75 to 450 µg/ml of Sodium phenylbutyrate and 25–150 µg/ml of Taurursodiol. The method’s LOD (Limit Of Detection) and LOQ (Limit Of Quantification) were 0.63 µg/ml, 0.21 µg/ml, and 2.1 µg/ml, 0.7 µg/ml for Sodium Phenylbutyrate and Taurursodiol, respectively. Conclusion: The proposed method to be fast, simple, feasible and affordable in assay condition. During stability tests, it can be used for routine analysis of production samples and to verify the quality of drug samples during stability studies.